A DISCOURSE ANALYSIS OF NEWS MEDIA ARTICLES ON THE POLISH ‘RULE OF LAW CRISIS’ - Dersley, Stephen (Comparative Legilinguistics, 2020)
The article identifies the discursive characteristics of news media texts covering Poland’s ‘constitutional crisis’. Following the conception of discourse presented in Laclau and Mouffe (1985), i.e. as an articulatory practice that conveys meaning through a structured system of positions and differences, the article highlights some features of English-language news media texts (e.g. from the Guardian, Telegraph, Economist, Financial Times, New York Times, Washington Post) that can be described as typical. The following features are identified: a lecturing tone, the use of structural oppositions, immediate rebuttals, misrepresentation, appeals to expertise, and the sovereignty taboo. These features are diagnosed as contributing to the narrow discursive range covered by news articles. To broaden the considerations, the article presents three conflicting positions from Polish legal theory that address the issues of constitutional courts, the rule of law and national sovereignty: Ryszard Piotrowki’s legal constitutionalism, Paweł Bała and Adam Wielomski’s Schmitt-inspired position, and Adam Sulikowski’s reading of the constitutional courts as an instrument of hegemonic discourse. In the conclusion it is suggested that news media discourse would benefit from demonstrating a greater awareness of other discourses, and from developing a more generous, balanced approach to presenting and addressing their claims.